SAMIN DAN KEHUTANAN JAWA ABAD XIX - Agus Purwanto (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
However, historically, Samin resistance by the end of XIX centery was sparked by two main issues, eg. forestry and taxation. Historical explanation on the fist issue, the relationship between Samin movement and forestry, is rarely discussed. On the other hand, Samin’s spiritual values—based on Adam religion teaching—are also frequently ignored from causalities discussion. The Samin’s Movement at XIX century showed the values they fiht for are religiosity, ethics of life, political ethics, farming knowledge, and forest point of view. The knowledge systems of farming based on their high appreciation for human being role in altering nature become food. On the other hand, the Java land, inclusive of forest in it is Entrusted by God creation of Pandawa to Javanese. Second, the history of management of Java Forest since Daendels’s era till appearance of Forestry Regulation 1865 and Agraria’s Law 1870 really progressively clarify interaction demarcation experience of among Samin with his forest.